2000
DOI: 10.1093/treephys/20.10.683
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations in xylem sap flux density in the trunk of orchard-grown, mature mango trees under changing soil water conditions

Abstract: Circumferential and radial variations in xylem sap flux density in trunks of 13-year-old mango (Mangifera indica L.) trees were investigated with Granier sap flow sensor probes under limiting and non-limiting soil water conditions. Under non-limiting soil water conditions, circumferential variation was substantial, but there was no apparent relationship between sap flux density and aspect (i.e., the radial position of the sensor probes on the trunk relative to the compass). Hourly sap flux densities over 24 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 17 publications
10
111
1
3
Order By: Relevance
“…A sensor that covered the whole sapwood depth, and integrated the variation in sapflow, would probably best account for the radial variations in sapflow density. As this necessitates a large number of sensors of variable length, an acceptable compromise would be to distribute two or more 2 cm long sensors throughout the entire depth of the sapwood [30]. It has been suggested that measurements with sensors that partly cover the conducting xylem should be scaled using a correction factor [13,25].…”
Section: Radial Variation Of Granier Measurementsmentioning
confidence: 99%
“…A sensor that covered the whole sapwood depth, and integrated the variation in sapflow, would probably best account for the radial variations in sapflow density. As this necessitates a large number of sensors of variable length, an acceptable compromise would be to distribute two or more 2 cm long sensors throughout the entire depth of the sapwood [30]. It has been suggested that measurements with sensors that partly cover the conducting xylem should be scaled using a correction factor [13,25].…”
Section: Radial Variation Of Granier Measurementsmentioning
confidence: 99%
“…Iida et al (2006) indicated that transpiration activity at this site was depressed by the lack of soil water when REW was less than 0.4. Thus, the soil water was sufficient and the variations in u were likely constant (Lu et al, 2000).…”
Section: Comparison Of Sap Flux Densities Observed By the Sfs And Tdpmentioning
confidence: 99%
“…Granier et al, 1996b;Köstner et al, 1998) and the azimuthal variations in u in the trunk, especially when growing in open canopy space like an orchard (Lu et al, 2000), must be determined. These variations of u can be measured by inserting a number of Granier sensors at the same height into a single tree.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Como se pode observar, em relação à bananeira, o mamoeiro representa um valor muito maior (˜11 vezes maior). Mesmo com valores de 0,06 m 2 de folha para cada cm 2 de área do xilema ativo, tal relação promoveu o valor bem elevado do fluxo de seiva (0,160 kg cm -2 de xilema ativo h -1 ), quando comparado a bananeira (0,015 kg cm -2 de xilema ativo h -1 ), pinheiro (0,019 kg cm -2 de xilema ativo h -1 ) (LU et al, 1995), em mangueira (0,035 kg cm -2 de xilema ativo h -1 ) (LU et al, 2000) e em algumas árvores tropicais (0,040 kg cm -2 de xilema ativo h -1 ) (GRANIER et al, 1996). Em bananeira, cultivada em condição de campo, LU et al (2002) realizaram medidas de FS as quais foram positivamente bem correlacionadas com algumas variaveis como radiação solar e evapotranspiração de referência.…”
Section: Neste Trabalho Com Mamoeiro Em Ambos Os T R a T A M E N T Ounclassified